Determination of Thallium(I) by Hybrid Mesoporous Silica (SBA-15) Modified Electrode - Geeta Rani; Sanjay Singh (International Journal of Electrochemistry, 2016)
Chemically modified mesoporous silica material (SBA-15) was used for the construction of Tl(I) selective carbon paste electrode. The best response was found with the electrode containing 10% modifier as electrode material. The electrode has a lower detection limit of 6.0 × 10−9 M in a working concentration range of 1.0 × 10−8–1.0 × 10−1 M. The selectivity coefficient calculated by match potential method (MPM) shows the high selectivity of electrode towards Tl(I) over other tested ions. The electrode was successfully applied as an indicator electrode for the titration of 0.01 M TlNO3 solution with standards EDTA solution and for sequential titration of mixture of different anions.